The thing in room 601 - Spenser, M. D.; Copyright Paperback Collection (Library of Congress) (U.S.A : Paradise Press, 1996)
Liam and Diane are vacationing with their mother in California and staying at a grand old hotel that turns out to be a hotel of horror.
Keywords: Horror tales; California -- Fiction; Young adult fiction